Remote Sensing Meets Agronomy: A Three-Year Field Study of Tritordeum’s Response to Enhanced Efficiency Fertilisers - George Papadopoulos; Ioannis Zafeiriou; Evgenia Georgiou; Antonia Oikonomou; Antonios Mavroeidis; Panteleimon Stavropoulos; Ioanna Kakabouki; Spyros Fountas; Dimitrios Bilalis (Agronomy, 2025)
This three-year field study evaluated the agronomic and physiological responses of Tritordeum to nitrogen fertilisation strategies under Mediterranean conditions using an integrated approach combining GDD-aligned phenological monitoring, UAV-based multispectral imaging, and soil analysis. Treatments included conventional urea, urea with a nitrification inhibitor (U+NI; DMPP-based), and urea with a urease inhibitor (U+UI; NBPT-based), compared to an unfertilised control. All nitrogen treatments significantly increased grain yield, reaching up to 2319 kg ha−1 under the nitrification inhibitor treatment (26% higher than the control), and protein content, which peaked at 16.04% under urea. Temporal analysis revealed that urea with nitrification inhibitors consistently enhanced plant height, canopy greenness, and pigment retention during flowering to ripening stages, with NDVI and MCARI peaking under U+NI in 2025. In contrast, urea with urease inhibitor promoted greater early-season biomass and height. Soil nitrogen retention was slightly improved under both EEF treatments, with no adverse effects on pH or salinity. The strong alignment between UAV-derived indices and agronomic traits supports their use for monitoring nitrogen response. These findings demonstrate the benefits of a stage-specific fertilisation strategy, deploying urea with nitrification inhibitor early and urea with urease inhibitor during peak vegetative growth, to improve nitrogen synchrony with crop demand and support sustainable crop management in Tritordeum.